Between actualism and the “standard theory of possible worlds” in Leibniz. - Gaiada, Griselda (ARFIL y UNL, 2020)
This article examines the scope and consistency of the “standard theory of possible worlds” in Leibniz’s thought. Its thesis is that actualism underlies the Leibnizian corpus as a background of tension that prevents the closure of the Leibnizian metaphysics of possible worlds from a single interpretation of the origin of things. To this end, a three-stage periodization of Leibniz’s explanations about the origination of the world is offered: firstly, a pure actualist model; secondly, an emanantist model and a creationist model, both coexisting and being interpretable in possibilist terms as well as in actualist terms; finally, an actualist model of “resultant will”. Our goal is not to take sides with some model or another, but only to make visible that all of them coexist in Leibniz’s writings as elements which dislocate within a sole and relatively closed interpretation.